1996
DOI: 10.1074/jbc.271.2.1209
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Anti-progestins Have Distinct Effects on Site-specific Phosphorylation of Human Progesterone Receptor

Abstract: , and Ser 345) are inducible by hormone agonist, while at least six others are basally phosphorylated and exhibit a general increase in response to hormone. In this study we have used high performance liquid chromatography phosphopeptide mapping and manual peptide sequencing to investigate how two different progestin antagonists, RU486 and ZK98299, affect site-specific phosphorylation of PR isolated from T47D breast cancer cells. As compared to the progestin agonist R5020, RU486 stimulated a similar increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Thus, phosphorylation seemed to be involved in PR-regulated gene transcription (Denner et al 1990. Studies on PR (Beck et al 1992(Beck et al , 1996 indicate that only Ser residues are phosphorylated (Takimoto & Horwitz 1993), and that Ser294 phosphorylation is strongly hormone dependent ). The cognate agonist and the intracellular messengers of GNRH1 (Denner et al 1990, Bai et al 1997) phosphorylate Ser294 and induce PR-mediated transcription (Zhang et al 1994), expression of PR-dependent GNRH1 self-priming proteins (Fink 1995, Tijssen et al 1997, preovulatory LH secretion (Fink 1988; Fig.…”
Section: Fsh Reduces Lh Secretion and Pr Phosphorylationmentioning
confidence: 99%
“…Thus, phosphorylation seemed to be involved in PR-regulated gene transcription (Denner et al 1990. Studies on PR (Beck et al 1992(Beck et al , 1996 indicate that only Ser residues are phosphorylated (Takimoto & Horwitz 1993), and that Ser294 phosphorylation is strongly hormone dependent ). The cognate agonist and the intracellular messengers of GNRH1 (Denner et al 1990, Bai et al 1997) phosphorylate Ser294 and induce PR-mediated transcription (Zhang et al 1994), expression of PR-dependent GNRH1 self-priming proteins (Fink 1995, Tijssen et al 1997, preovulatory LH secretion (Fink 1988; Fig.…”
Section: Fsh Reduces Lh Secretion and Pr Phosphorylationmentioning
confidence: 99%
“…While the oestrogen-induced LHRH selfpriming involves intracellular cAMP/PKA crosstalk with PR (Turgeon & Waring 1991, Waring & Turgeon 1992, the mechanism of TX-induced LHRH self-priming is not completely known. The involvement of PR is well documented, as oestrogen-and TX-induced LHRH selfpriming can be suppressed (Sánchez-Criado et al 2004) by blockade of PR action with P 4 antagonists RU486 or ZK299 (Beck et al 1996). In fact, both LHRH self-priming and potentiation of LHRH-stimulated LH secretion by priming substances different from LHRH during the priming period (Pickering & Fink 1976) can be considered as physiological markers of PR activation in the gonadotrope.…”
Section: Discussionmentioning
confidence: 99%
“…Both P 4 (Denner et al 1990, Takimoto & Horwitz 1993, McDonnell 1995 and LHRHdependent cAMP/PKA intracellular signal , Bai et al 1997, Rowan et al 2000 can phosphorylate the PR, a phosphoprotein transcription factor (Evans 1988, Mangelsdorf et al 1995 that, upon phosphorylation, results in activation, transcription and regulation of gene expression (Beck et al 1996). The absence of effect of P 4 and adenylyl cyclase activator FSK on TX-treated pituitaries or pituitary cells due to E 2 might well reveal a deficient basal or liganddependent phosphorylation response of PR (Takimoto & Horwitz 1993) to the physiological ligands P 4 or PKA (Rowan et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested mechanisms by which steroid antagonists inappropriately activate transcription. Cross-talk between antagonist-occupied steroid receptor and cell surface signaling pathways such as the activation of PKA and PKC pathways can switch the antagonist into an agonist (Beck et al, 1996;Sartorius et al, 1994). More recent studies revealed that antagonist-occupied steroid receptors are the targets for the action of endogenous coregulators (Jackson et al, 1997;Simth et al, 1997;Takimoto et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Type II antagonist, represented by RU486, is capable of inducing high affinity association of PR with target DNA. The DNA binding of RU486 and other type II antagonist is often associated with agonist activities under some circumstances (Meyer et al, 1990;Nordeen et al, 1993;Beck et al, 1996). The presence of cell signaling molecules such as cAMP, enhances these agonist effect (Nordeen et al, 1993;Truss et al, 1994;Sartorius et al, 1994).…”
mentioning
confidence: 99%